Flipped Classroom in Information Technology Education: A Systematic Literature Synthesis of Its Impact on Self-Regulated Learning and Problem-Solving Skills - Muh. Fadhil Supriadi; Supriadi (Universitas Cahaya Prima, 2026)
The rapid development of digital technology has significantly transformed educational practices, particularly in Information Technology Education, requiring innovative instructional approaches that foster 21st-century skills such as self-regulated learning and problem-solving. One such approach is the Flipped Classroom, which shifts content delivery outside the classroom and utilizes in-class time for active, student-centered learning. This study aims to synthesize existing research on the implementation of the Flipped Classroom and its impact on self-regulated learning and problem-solving skills. This study employed a Systematic Literature Review (SLR) approach guided by the PRISMA framework. Data were collected from Scopus, Web of Science, ERIC, and Google Scholar. From an initial pool of 320 articles, 25 studies were selected through a rigorous screening and eligibility process based on predefined inclusion criteria. The findings indicate that the Flipped Classroom has a positive impact on students’ self-regulated learning by promoting learning autonomy, responsibility, and the ability to manage learning processes. It also enhances problem-solving skills by facilitating higher-order thinking through interactive and collaborative classroom activities. Moreover, the results reveal that self-regulated learning and problem-solving skills are interconnected, where improved self-regulation contributes to more effective problem-solving performance. However, the effectiveness of this approach is influenced by factors such as students’ readiness, access to technology, and instructional design. In conclusion, the Flipped Classroom is a promising approach for enhancing key competencies in Information Technology Education and offers valuable implications for future research and practice.